Legal Policy of Protection COVID-19 Patients in Hospitals - Tri Hartini (Journal of Human Rights, Culture and Legal System, 2022)
The government has issued a number of measures in response to Covid-19, but these policies do not ensure patient rights as defined by the constitution. This is a juridical-normative study with a focus on legislation. The results indicated that legal protection for Covid-19 patients at home was accomplished in three ways: first, through civil legal remedies based on civil provisions; second, through criminal legal remedies based on medical practice; and third, through legal administration efforts that can be reported to the Council. Indonesian Medicine and the Honorary Council of Indonesian Medical Disciplines The rules and regulations controlling the protection of the law have an effect on the legal protection of patients; they compel health workers delivering health services to respect applicable laws and regulations.